2004
DOI: 10.1007/s00705-004-0419-3
|View full text |Cite
|
Sign up to set email alerts
|

The resurgence of Shamonda virus, an African Simbu group virus of the genus Orthobunyavirus, in Japan

Abstract: Six virus isolations were made from Culicoides biting midges and blood samples of sentinel cattle in Kagoshima and Miyazaki Prefectures, the southern part of Japan, in 2002. Serological and genetical tests identified these viruses as isolates of Shamonda virus (SHAV), which belongs to the Simbu group of the genus Orthobunyavirus of the family Bunyaviridae. Initially, SHAV was isolated from cattle and Culicoides biting midges in Nigeria in the 1960s, and its presence has not been reported until this study. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 16 publications
1
32
0
1
Order By: Relevance
“…These results may reflect a lower seroprevalence in goats in general. Given that goats, in contrast to cattle and sheep, are often housed indoors, and the SBV is supposedly transmitted by Culicoides vectors, like other viruses of the Simbu serogroup [2,13,14], this lower seroprevalence would not be surprising.…”
Section: Discussionmentioning
confidence: 99%
“…These results may reflect a lower seroprevalence in goats in general. Given that goats, in contrast to cattle and sheep, are often housed indoors, and the SBV is supposedly transmitted by Culicoides vectors, like other viruses of the Simbu serogroup [2,13,14], this lower seroprevalence would not be surprising.…”
Section: Discussionmentioning
confidence: 99%
“…The most similar sequences were from a Shamonda virus detected in cattle in Japan (S segment; INSDC accession no. AB183278; 97% identity) ( 2 ), an Aino virus discovered in cattle in Japan (M segment; accession no. AB542971; 71% identity) ( 3 ), and an Akabane virus found in cattle in Japan (L segment; accession no.…”
Section: The Studymentioning
confidence: 99%
“…Recent phylogenetic analyses have demonstrated that SBV is most closely related to viruses of the species Sathuperi virus and is not a reassortant with other species of the Simbu serogroup [1], [3]. Viruses of this serogroup, including Akabane (AKAV) and Aino virus, have previously been isolated from pools of livestock associated Culicoides biting midges in Japan where the vector most clearly implicated is Culicoides oxystoma [4], [5], [6]. Vector competence studies for these arboviruses are most complete for AKAV, particularly in Australia where the role of Culicoides brevitarsis in transmitting and spreading the virus has been characterized in detail [7], [8].…”
Section: Introductionmentioning
confidence: 99%